WHEN RELIGION GOES TO THE WORKPLACE: The Sociology of Knowledge about Religiosity (JOURNAL OF INDONESIAN ISLAM, 2013)
This paper aims to examine the religiosity of Muslim professional workers and the position of religion for them in their daily life. This paper takes two steps: first, studying the religiosity of those Muslim professional workers within their workplace by using Peter L Berger’s framework of the Construction of Social Theory; second, examining the thoughts and expressions of those workers when they are faced with a dilemma in work conditions through in-depth interview. This study concludes that the Muslim professional workers who live in the modern society with diverse conditions of a dilemma between the religious values and the demands of expertise in their job tend to be more faithful to their religious beliefs. Berger’s thesis about secularization does not occur in the case of workers of this kind. Religion stays functional for these workers through deconstruction strategy as it is assumed by Derrida. The so-called “traces of God” can still be seen in these workers in Surabaya.